HEALTH CARE EDUCATION ON IMPORTANCE OF DENTURE THROUGH VIDEO ANIMATION IN DINOYO AND MOJOLANGU MALANG - Fatima, Fatima; Hapsari, Diwya Nugrahini; Irgananda, Citra Insany; Wardani, Sinta Candra; Pratama, Hafizh Haidar; Laksono, Oswalda Rena Krismaningrat (Caring: Jurnal Pengabdian Masyarakat, 2023)
AbstractTeeth have an important function for human life in terms of aesthetics, mastication and speech functions. Losing some teeth or even all teeth can result in a reduction or loss of these functions. A person can use dentures made by a dentist to replace missing teeth, because losing teeth in the mouth if left too long has the potential to adversely affect the condition of other teeth. The purpose of this research is to increase public understanding of the importance of making dentures so as to minimize the risk of losing teeth. The design is Quasy experimental. Samples were taken using a purposive sampling technique, which is posyandu cadres at the Dinoyo Health Center and Mojolangu Health Center. Statistical data were analyzed using the Wilcoxon test.  The results showed that education on the importance of making dentures in the community through animated videos at the Dinoyo and Mojolangu Health Centers showed good results. There was an increase in the pre-post test scores of the extension participants. Based on the statistical test, the value of sig p=0.000 was obtained, which means that there was a significant change. It can be concluded that education about the importance of making dentures in the community for posyandu cadres delivered through animated videos shows good results and significantly increases the participants' understanding of the importance of making dentures in the community.